"Verbalização do sagrado" em tempos de fronteira: a recepção do Concílio Vaticano II no Maranhão, 1959-1979 - Santos, Sérgio Ricardo Coutinho dos (2015)
This study look into the participation of the bishops of Maranhão in the Second Vatican Council (1959-1965) and how they did, along with other social and ecclesial actors, the reception of this ecclesial event in their “local Churches” (diocesis). This process, within a context of expansion of “economic frontier” and formation of a new oligarchic domination in the conduct of regional and local politics, led by José Sarney, between the years 1959 and 1979. The chronological marking will the convening of Vatican II until the holding of IIIª General Conference of Latin American Bishops in Puebla (Mexico). Our theoretical and methodological proposal revolves around the concepts of “frontier” (José de Souza Martins), of “historical consciousness” (Jörn Russen), of “historicity regime” (Reinhart Koselleck and François Hartog), and “communicative action” and “post-conventional moral conscience” (Jürgen Habermas and Lawrence Kohlberg). The "Vatican II" event and its reception by the subjects-agents (bishops, priests, religious, pastoral workers and lay people) of the local Churches (diocesis) in Maranhão, allowed greater reflective socialization within the lived world (“verbalization of the sacred”), relying on the resources of the discussion. And so, it made in the perspective of action oriented to mutual understanding, and hinged on two principles of ecclesiastical organization: the episcopal collegiality and the base of synodality. Thus, the Catholic Church in Maranhão took on a new historical consciousness: the post-conventional.